You are on page 1of 19

INFORMATION AND COMMUNICATIONS UNIVERSITY

SCHOOL OF ENGINEERING
(DEPARTMENT OF COMPUTER FORENSICS)

NAME

JACK MAMBWE

SIN

1304944224

PROGRAM

: BSC. INFORMATION SECURITY AND

COMPUTER FORENSICS

COURSE

: HIGHER MATHS 2

SEMISTER

: TWO

ASSIGNMENT NO.

:1

Question 1
a

P = 5000x - 125x2
(dp/dx)>0, for profit to increase
P=5000x-125x2
0>5000-250x
if x>20; then

Profit increases in the interval x >20

For profit to reduce dp/dx <0


0<5000x-125x2
X<20

Profit decreases in the interval x<20


For maximum profit x=20
dp/dx =5000x-125x2
x\=20

Maximum profit will be attained when x = 20

Question 2
y = f(x) = x4 6x3 + 12x2 8x

y
x = 0 at turning points on the curve
y
4
3
2
x (x 6x + 12x 8x)
= 4x3 18x2 + 24x2 8
If f(x) is divided by (x a) the f (a) = 0 and (x a) is a factor of f(x)
If x = 2; then
f (2) = 4(2)3 18(2)2 + 24(2)2 8
= 32 72 + 48 8
=0
Hence (x -2) is a factor of 4x3 18x2 + 24x2 8
If x = 1/2; then
f (1/2) = 4(1/2)3 18(1/2)2 + 24(1/2)2 8
= 1/2 9/2 + 12 8
=0
Hence (x - 1/2) is a factor of 4x3 18x2 + 24x2 8
If Dy2/Dx2 = 0, the stationary point is point of inflexion
Dy2/Dx2 (4x3 18x2 +24 xs2 8)
= 12x2 36x + 24
When x = 2;
Dy2/Dx2 = 0
When x =1/2;
Dy2/Dx2> 0, hence (1/2, -27/16) is minimum
When x = 0; y = f(x) = x4 6x3 + 12x2 8x

= (0)4 6(0)3 + 12(0)2 8(0)


=0
Hence, the equation of the tangent at point of inflexion
at the point (2,0) , gradient is 0

y=mx+c
0=c
Equation
Y=0
And
Y=-27/16
Question 3

2x
1+ x 2
Y=

sin 1
sin y=

2x
1+ x2

(1)

Differentiating with respect to x, we get


1+ x 2

Let u= 2 x

And u=siny
du=cosy
dy
Now;
Cosy=

1sin2 y

1(

2x 2
)
1+ x 2

dy/du=

1
2

1(

2x
)
1+ x 2

1+ x 2

u= 2 x

d 2x
(
)
dx 1+ x2

( 1+ x 2 ) .22(2 x 2)
dy
cosy =
2 2
dx
(1+ x )

2 ( 1+ x 2 )4 x 2
(1+ x2 )2

2(1x 2)
dy
cosy=
dx
(1+ x 2 )2
2

dy 2 ( 1x ) 1
=
.
dx ( 1+ x 2 )2 cosy
=
1x 2
Cosy= 1+ x 2

dy 2 ( 1x )
=
.
dx ( 1+x 2 )2

1(

2x 2
)
2
1+ x

b
2

y= ( x +1 tan x
By product rule, we get;

x
d ( 2 )
x +1
dx
d
y ' =( x 2+1 )
dx

tan 1 + tan1 x .

=(

x 2+1 .

Hence, y = ( x + tan x = 1+ 2 x tan

1
+ tan1 x (2 x)
(x +1)
2

c
y= sin
sin y =

1x2

1x 2

Differentiating the above equations gives;

d
d
siny= ( 1x 2 )
dx
dx
dy
x
. cosy=
dx
1x 2
But Cosy=

dy
1
=
dx 1x 2 .

1
1sin2 y

1sin2 y

1
1
2
= 1x . x

1
1
Hence, y = 1x 2 . x

d
y= e

sin x+tan x

let U= sin x+ tan x

du
1
=cosx+ 2
dx
x +1

, Y=

eu

dy u
=e
du

By chain rule;

dy dy du
= .
dx du dx
cosx+

1
x +1
2

dy
=
dx

={

eu

( x2 +1 ) cosx+1
2

x +1

}. e

sinx+ tan x

Hence, y= e

sin x+tan x

={

( x2 +1 ) cosx +1
2

x +1

}. e

sinx+ tan x

e
2

Y= ln( x +tanx+ arcCscx

dy
1
d
= 2
. ( x 2+tanx+ arcCscx)
dx x +tanx+arcCscx dx

1
x +tanx+arcCscx
2

2 x+sec 2 xcotxCosecx
x 2 +tanx+arcCosecx

Hence, y = ln ( x +tanx+ arcCscx

Question 4

Show that

. { 2 x + sec xcotxCscx }

2 x +sec 2 xcotxCosecx
x 2 +tanx+arcCosecx

(nr )

n
(nr
)

Let n= 10, and r =3

(nr )

Therefore,

(103)

n
(nr
)

and

10
(103
)

Taking the RHS,

10
(103
)

(107 !!)

10 x 9 x 8 x 7 x 6 x 5 x 4
= 7 x 6 x 5 x 4 x 3 x 2 x 1 =120

Question 5
a

(x 2)5
a = x; b = -2
=

(50)

(x5 )(-2)0 +

(55 )

(x0)(-2)5

(51 )

(x4 )(-2)1 +

(52 )

(x3 )(-2)2 +

(53)

(x2 )(-2)3 +

(54 )

2)4
+

= (1) (x5) + (5) (-2x4) + 10(4x3) + (10) (-8x2) + (5) (16x) + (1) (1) (-32)

Hence, (x - 2)5= x5 -10x4 + 40x3 - 80x2 + 80x 32


b

(x1/x)6 = x/x = 1
Hence, (x 1/x) 6= 1

(2x 1)5
a = 2x; b = -1
25

(50 )

+ 21

(x5 )(-1)0 + 24

(54 )

(51)

(x1 )(-1)4 + 20

(x4 )(-1)1 + 23

(55)

(x0)(-1)5

(52)

(x3 )(-1)2 +22

(53)

(x2 )(-1)3

(x1 )(-

= 32(1)(x5) + 16(-5x4) + 8(10x3) + 4(-10x2) + 2(5x) + 1(-1)

Hence (2x 1)5 = 32x5 80x4 + 80x3 - 40x2 +10x 1

(x 3y)4
a = x; b = -3y
(-30

4
0

+ (-3)4

()
(44 )

(x4 )(y)0 + (-3)1

(41 )

(x3)(y)1 + (-3)2

(42 )

(x2)(y)2 + (-3)3

(x0)(y)4

= 1(1)(x4 )(y)0 -3(4)(x3 )(y)1 + 9(6)(x2 )(y)2 -27(4)(x1)(y)3 + 81(1)(x0 )(y)4


= x4- 12x3y+54x2 y2 - 108xy3 + 81y4
Hence (x 3y)4 = x4 - 12x3y+ 54x2 y2 - 108xy3 + 81y4

nth term is given by

n
(k 1
)

an-(k-1) bk-1

Fourth term in the expansion of (x -2y)7, taking k to be 4:

7 4
x )(-2y)3
3

()
= -23

7 4
x )(y)3
3

()

= -8(35)(x4)(y)3
= -280x4y3
Hence, fourth term in expansion of (x -2y) is -280x4y3
b Seventh term in the expansion of (x2 1/x)9, taking k to be 7:

(43 )

(x1)(y)3


9 23
x ) (1/x)6
6

()
=

9 2 3 -1 6
x ) (x )
6

()

= 84(x6) (x-6)
= 84(x) 6+ (-6)
= 84(x) 0
= 84
Hence, seventh term in expansion of (x2 1/x)9is 84

Fifteenth term in the expansion of (2 1/x)19, taking k to be 15 is:

19 5
2 )(-1/x) 14
14

( )
= 25

19
-1/x) 14
14

( )

= 32(11628) -1/x) 14
= -372096/x14
Hence, fifteenth term in the expansion of (2 1/x) 19 is -372096/x

n ( n1 ) x
( 1+x ) =1+ nx +
+
1!
2!
n

(1 2x)1/2
2 x

2x

3
1
1/2 1
2
1
( )( x)
1 /2
2
( 12 x ) =1+
+
1!

( )

= 1 + x x2/2 + (-3/6)(x3)
= 1 + x x2 - x3

Hence, (1 2x)1/2 = 1 + x x2 - x3 . The expansion is valid in the range |


2x| < 1 or x <
b (3 + x)-1 = [3(1 + x/3)]-1
x /3

x /3

= 3-1[
]

3
1 (11 )
(1)(x /3)
1+
+
1!
= 1/3[1 x/3 + x2/9 x3/27]
= 1/3 1/9x + 1/27x2 71x3
(3 + x)-1 = 1/3 1/9x + 1/27x2 71x3. The expansion is valid in the range x/3 <
1 or |x| < 3

x + 2/x 1 => [x(1 + 2/x)]/[x(1 1/x)]


=> [x (1 + 2/x)] * [x (1 1/x)]-1
2 /x

2 /x

[x (1 + 2/x)] = x1 [
]

3
1 ( 11 )
(1)(x )
1+
+
1!
= x + x2 .... (i)
1/ x

1/ x

[x(1 1/x)]-1 = x-1[


]

3
1 ( 11 )
(1)( x )
1+
+
1!
= 1/x [1 x + 3/2x2 1/x3]
= 1/x 1 + 3/2x3 1/x4 .... (ii)
Hence, x + 2/x 1 => (x + x2) (1/x 1 + 3/2x3 1/x4)
= (2) (3/2x3 1/x2) => 3/x3 2/x2
x + 2/x 1 = 3/x3 2/x2. The expansion is valid in the range 2/x < 1 or 2 <x
and 1/x < 1 or 1 < x

d 1/(1 + x)1/2 => (1 + x)-1/2

=
3
1
1/2 1
2
1
( )(x )
2
1+
+
1!

( )

=1x+

3
1 /2

( 32 )

= 1 - x + 3/2x2 45/8x3
1/ (1 + x)1/2 = 1 - x + 3/2x2 45/8x3. The expansion is valid in the range |x| < 1
or -1 < x < 1

3
a

2
3 x3 2
3 x3
2
2
2
( x + 4 ) dx =>( x +4 ) dx - ( x +4 ) dx

3 x3
= ( x 2 +4 ) => 3x -

12 x
x 2 +4

(by long division)

12 x
3 x3 2
( x 2+ 4 ) dx= 3x dx - x 2 +4

2x
3
2
2 x - 6 x 2 +4

2
- ( x 2 +4 ) dx

1
dx - 2( x +4 ) dx
2

2x
6 x 2 +4 ; let u = x2 + 4
du
dx

= 2x

1
3
2 x du
2
2 x - 6 u 2 x - 2( 4( x /2)2+ 1 ) dx

3
1
2
2 x -6 u

3
1
x
2
-1
2 x - 6 ln u - 2 tan ( 2 ) + c

1
2
du - 4 ( ( x /2)2 +1 ) dx

3 x3 2
Hence, ( x 2+ 4 ) dx =

ii

4x
( 2)
( x+ 2 ) dx

a2 u2 => u = a sin x

3
2
2
2 x - 6 ln(x + 4) -

1
2

x
tan-1 ( 2 ) + c

a2 = 4 = 2
u2 = x2 = x
Hence;
x = 2 sin x
x
2 = sin x
dx = 2 cos x
4

4 x2)= - (2 sin x)2)


4
= - 4 sin2 x)
= 4 (1- sin2 x))
4
= cos2 x)

Hence, 4 x2)= 2 cos x

4x
4x

( 2)

( x+ 2 ) dx =
)

xdx +2 dx

(2 sin x )(2 cos x)+2 cos x


2 cos x
= -2 cos x + x + c

4x
4x
( 2)
Hence, ( x+ 2 ) dx = - ( 2) + x + c

iii

3 x3 2
(4 x2 +9)3 /2 dx

b z3 + 8i => z = 0 + 8i

r = |z| = 02 + 82)

r = |z| = 8
= Arg z =

y
x

8
= tan -1 0
= 90
Zn = rc i s
= rc i s1/n
= r1/nc i s (

+360 k
)
n

Wk =W0 = 81/3 c i s (

90+360(0)
)
3

= 2 c i s (30)
=2 (cos 30 + i (sin 30))

=2(

3
2

1
i
+ 2 )

= 3+ i
Hence, Wk =W0 = 3 + i

Wk =W1 = 81/3 c i s (

90+360(1)
)
3

= 2 c i s (150)
=2 (cos 150 + i (sin 150))

=2(

3
2

1
i
+ 2 )

= 3 + i
Hence, Wk =W1= 3 + i

Wk =W2 = 81/3 c i s (

90+360(2)
)
3

= 2 c i s (270)
=2 (cos 270 + i (sin 270))
=2(0 + i(1) )
= 02i
Hence, Wk =W2= 02i

Wk =W3 = 81/3 c i s (

90+360(3)
)
3

= 2 c i s (390)
= 2 (cos 390 + i (sin 390))

= 2(

3
2

1
i
+ 2 )

= 3+ i
Hence, Wk =W3= 3 + i